Performance of metal and polymeric O-ring seals during beyond-design-basis thermal conditions. (April 2017) - Yang, Jiann C.; Hnetkovsky, Edward; Rinehart, Doris; Fernandez, Marco; Gonzalez, Felix; Borowsky, Joseph
Abstract: This paper summarizes the small scale thermal exposure test results of the performance of metallic and polymeric O-ring seals typically used in radioactive material transportation packages. Five different O-ring materials were evaluated: Inconel/silver, ethylene-propylene diene monomer (EPDM), polytetrafluoroethylene (PTFE), silicone, butyl, and Viton. The overall objective of this study is to provide test data and insights to the performance of these O-ring seals when exposed to beyond-design-basis temperature conditions due to a severe fire. Tests were conducted using a small-scale stainless steel pressure vessel pressurized with helium to 2 bar or 5 bar at room temperature. The vessel was then heated in an electric furnace to temperatures up to 900 °C for a pre-determined period (typically 8 h–9 h). The pressure drop technique was used to determine if leakage occurred during thermal exposure. Out of a total of 46 tests performed, leakage (loss of vessel pressure) was detected in 13 tests.